EFEKTIVITAS PROGRAM SEMBAKO DI DESA ENTALSEWU KECAMATAN BUDURAN KABUPATEN SIDOARJO - Sofi Intan Febrianti; Isnaini Rodiyah (Halu Oleo University, 2025)
This research aims to analyse and describe the effectiveness of the Sembako Program in Entalsewu Village, Buduran Subdistrict, Sidoarjo Regency. The research method used is descriptive qualitative, with data collection techniques including interviews, observation, and documentation. Data analysis employs the Miles and Huberman model, which consists of data collection, data reduction, data display, and conclusion drawing. The research findings are reviewed based on five indicators. First, the program success indicator shows that the program was implemented on time with the support of active and responsive officers. Second, the target achievement indicator reveals that the program's recipients were selected based on outdated data and community proposals, with issues resolved through coordination with the Social Services Department. Third, the satisfaction indicator indicates that the community was fairly satisfied with the information and assistance received, although there were variations in the timing of aid disbursement. Fourth, the input and output indicator shows that officers have conducted technical training on the SIKS-NG application, but the outcomes of these efforts still need improvement. Fifth, the overall goal achievement indicator demonstrates that the village government has been responsive in addressing challenges through cross-sector coordination.